The effect of a low dose hydrogen-oxygen mixture inhalation in midlife/older adults with hypertension: A randomized, placebo-controlled trial - Liu, Boyan; Jiang, Xue; Xie, Yunbo; Jia, Xiubin; Zhang, Jiashuo; Xue, Yazhuo; Qin, Shucun (Frontiers in Pharmacology, 2022)
Objective: To explore the effect of a low-dose hydrogen–oxygen (H2-O2) mixture inhalation in midlife/older adults with hypertension. Methods: This randomized, placebo-controlled trial included 60 participants with hypertension aged 50–70 years who were randomly divided into Air group (inhaled placebo air) or H2-O2 group (inhaled H2-O2 mixture (66% H2/33% O2)). Participants in both groups were treated 4 h per day for 2 weeks. Four-limb blood pressure and 24-h ambulatory blood pressure were monitored before and after the intervention, and levels of plasma hormones related to hypertension were determined. Results: A total of 56 patients completed the study (27 in the Air group and 29 in the H2-O2 group). The right and left arm systolic blood pressure (SBP) were significantly decreased in H2-O2 group compared with the baseline levels (151.9 ± 12.7 mmHg to 147.1 ± 12.0 mmHg, and 150.7 ± 13.3 mmHg to 145.7 ± 13.0 mmHg, respectively; all P < 0.05). Meanwhile, the H2-O2 intervention significantly decreased diastolic nighttime ambulatory blood pressure by 2.7 ± 6.5 mm Hg (P < 0.05). All blood pressures were unaffected in placebo group (all P > 0.05) When stratified by age (aged 50–59 years versus aged 60–70 years), participants in the older H2-O2 group showed a larger reduction in right arm SBP compared with that in the younger group (P < 0.05). In addition, the angiotensin II, aldosterone, and cortisol levels as well as the aldosterone-to-renin ratio in plasma were significantly lower in H2-O2 group compared with baseline (P < 0.05). No significant differences were observed in the Air group before and after the intervention. Conclusions: Inhalation of a low-dose H2-O2 mixture exerts a favorable effect on blood pressure, and reduces the plasma levels of hormones associated with hypertension on renin-angiotensin-aldosterone system and stress in midlife/older adults with hypertension.